TEACHING VOCABULARY WITH A SUPPLEMENTARY TEXTBOOK: “DAHANI DAHANAI LEARNING ENGLISH” TO IMPROVE STUDENT’S ACADEMIC ACHIEVEMENT - Thesaloga, Rino; Perdana, Indra; Misrita, Misrita (Journal Compound: Improving the Quality of English Education, 2022)
The aim of this quantitative research is to measure the effectivity of the developed supplementary English textbook in improving the student’s academic achievement through vocabulary learning. The participants are 51 seventh graders students of SMPN 1 Gunung Bintang Awai. This is a preexperimental study hence only one group is involved. The samples received the treatment: learning English vocabulary using task-based Dahani Dahanai Learning English textbook for three weeks with total 6 sessions. Two identical tests were prepared as the pretest and posttest to record the student’s score before and after the treatment. The data received from the instruments were compared and analyzed with paired sample t-test and N-gain score test. The t-test found that the improvement in score is significant, with sig. value 0.000, which is less than 0.05. Whereas the Ngain score test revealed a modest gain with a g. value of 0.31. This signifies that the product has a moderate impact on kids' academic progress.